A vinylogous Michael reaction of 2-furanone dimers with α, β-unsaturated nitroolefins for constructing chiral γ, γ-disubstituted butenolides. Issue 19 (18th May 2020) - Bai, Zhushuang; Zhang, Cairong; Chen, Yongyi; Liu, Aiqin; Wang, Xinyu; Yan, Chuna; Liu, Xuechao; Zhang, Xiaoru; Li, Ying; Yuan, Ye; Ge, Zemei; Pang, Jingxiang; et al.
Abstract : An asymmetric vinylogous Michael reaction of 2-furanone dimers with α, β-unsaturated nitroolefins utilizing bifunctional thiourea as a catalyst has been developed, which provides an easy access to a wide range of chiral γ, γ-disubstituted butenolides. Abstract : An efficient bifunctional thiourea-catalyzed asymmetric vinylogous Michael addition of 2-furanone dimers to α, β-unsaturated nitroolefins has been developed to afford functional chiral γ, γ-disubstituted butenolides in good yields (up to 95%) with good to excellent stereoselectivity (up to >20 : 1 dr, 99% ee). DFT calculations were carried out to explain the high stereoselectivity.